Pancasila Sebagai Fondasi dalam Pembentukan Hukum Tata Negara di Era Reformasi: Pancasila as a Foundation in the Formation of Constitutional Law in the Reform Era - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Royyan Ulya Safiinatun Najah; Rachmatullaili Zulaikhah Suyuti; Athifah Amani Nengrum (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
Pancasila, as the ideological basis of the Republic of Indonesia, plays a fundamental role in the formation and application of constitutional law, especially in the reform era that began in the late 1990s. Major transformations in Indonesia's political and legal system during this period, including the amendment of the 1945 Constitution, the renewal of laws, and the reform of state institutions, posed challenges in maintaining the relevance and application of Pancasila principles. This research aims to explore how Pancasila was integrated in the new legal and constitutional policies and to assess the impact of legal reforms on the implementation of Pancasila values. Using academic sources, empirical data, and up-to-date theoretical analyses, this research identifies the challenges faced and possible solutions to ensure Pancasila principles remain relevant and effective. The results show that although Pancasila faces various challenges, it remains a vital ideological foundation in Indonesia's legal system. In conclusion, Pancasila as an ideological foundation cannot be separated from the life of society and the state.